BUSINESS MODEL INNOVATION STRATEGY THROUGH VALUE PROPOSITION REDESIGN IN CORPORATE FINANCING: A CASE STUDY OF EVERGREEN FINANCE - Virgine, Rizky Monica (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study examines how a corporate financing institution can redesign its business model to regain competitiveness in the working capital segment. Evergreen Finance, a multi-finance company in Indonesia, has experienced declining new customer acquisition and stagnating revenue for its working capital, despite overall portfolio growth. Using Business Model Innovation (BMI) as the overarching lens and Value Proposition as the analytical engine, this study diagnoses the misfit between Evergreen Finance’s “procedurally safe” model and the evolving needs of corporate clients in time-critical industries such as coal and logistics. A qualitative single-case study approach is adopted, combining a fishbone analysis with in-depth semi-structured interviews of two key corporate clients representing an “at-risk yet active” user and a “loyal but in-dispute” client. The data are analyzed thematically and mapped onto the VPD framework to construct a Customer Profile (jobs, pains, gains) and an Internal Value Map. A systematic fit–misfit analysis across four BMI pillars such as Value Proposition, Service Operations, Market Interface & Relationships, and Finance reveals severe gaps in speed assurance, policy flexibility, collateral capability, loyalty recognition, and financial logic. The study proposes a three-pillar value proposition (Speed, Capability, Loyalty) supported by dual lane FMU design, conditional disbursement, relationship-aware collection, risk-based revaluation, and property-backed FMU products. The paper concludes with managerial implications for Evergreen Finance and theoretical contributions for business model innovation in emerging-market multi-finance industries.   Keywords: business model innovation; value proposition design; working capital financing; multi-finance; corporate financing; Indonesia.